ANTECEDENTES DOS BENEFÍCIOS PERCEBIDOS DE COMPLIANCE ÀS POLÍTICAS DE PROTEÇÃO DE DADOS PESSOAIS NAS ORGANIZAÇÕES - SANTOS, JULIANA GRACIELA DOS (2016)
Personal data protect procedures are organizational tools that properly used by the employee help in the prevention and personal data protect within a safety and transparency organizational limit. This study analyzed the factors that have influenced the perception of the employees of Brazilian organizations about perceived benefits of compliance on the policies established in the prevention and protection of personal data. The research was conducted through a quantitative research approach with analysis of structural equations and the study data were collected through a survey tool to obtain a valid sample of 220 respondents. The study concluded that trust in organization and the risk of loss of personal data are stimulus that positive influence the benefits perceived of the compliance. The results also show that the employees who had your data improperly used, reduces your credibility in organizational controls and increases their perceived risk of privacy loss. The result of the study can help organizations managers to achieve greater adherence of employees with regard to personal data protection policy of organization in which they work, in addition to demonstrate the importance of credibility in internal controls and trust in the organization as predictors of perceived benefits of compliance.